PENGARUH KINERJA PENYULUH PERTANIAN TERHADAP PERILAKU PETANI PADA PENERAPAN TANAM JARWO 2:1 DI KECAMATAN BANJARANGKAN KABUPATEN KLUNGKUNG - I Ketut Arya Sudiadnyana; I Gede Setiawan Adi Putra (Universitas Udayana, 2019)
ABSTRACT Banjarangkan District, Klungkung received the GP-PTT program with assemblies of Jajar Legowo 2: 1 planting technology where agricultural extension agents were the spearhead of program implementation. This study aims to: (1) determine the performance of agricultural extension workers according to farmers, (2) analyze the influence of extension workers' performance and farmer characteristics on farmer's behavior, (3) analyze the influence of farmer behavior on productivity. This research was conducted in Banjarangkan District, Klungkung Regency. Data collection was carried out from May to August 2018. The population in this study were farmers who participated in the GP-PTT program that used 2: 1 jajar legowo planting methods. The number of samples used was 96 farmers who were determined using the Slovin formula with a confidence level of 10%. Samples were taken using purposive sampling propotional technique. Data analyzed using descriptive analysis methods and statistics using version 3.0 SmartPLS. The results of the study show: (1) the performance of extension agents in Banjarangkan District is in a good category; (2) the instructor's performance and farmer's characteristics have a significant effect on farmer's behavior; (3) farmer's behavior has a significant effect on productivity. Suggestions that can be given in this study are: (1) the performance of the instructor in guiding the group's definitive plan needs to be improved; (2) non-formal education in the form of training and field schools whose intensity needs to be improved; (3) government support for financing non-formal education needs to be improved; (4) development of other research needs to be done with different constructs and indicators to support the government in taking policy.